Narrative palette in the story "Force of circumstances" by W.S. Maugham (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The short story “The Force of Circumstance” by W. S. Maugham is being ana-lyzed from the point of view of narratology in the given article. The subjects of narra-tion and the dominating narrative patterns are distinguished in it. The narrative peculi-arities of a piece of prose as the means of conveying the emotions, shades of the mood, life credo of the author, and common human values are investigated. The structure of narration typical of the literary works of such a genre is being traced here.
Keywords: narratology; narrative patterns